Ethanol additive addition to gasoline: viscosity investigation using stokes law linear regression - Taufik Ulhakim, Muhamad; Karina Chintya, Lestari; Suhara, Ade; Bertolomeus Haryanto, Agung; Ummah, Auliya Rahmatul; Nur, Arip Syaripudin (Jurnal Teknik Mesin Mechanical Xplore, 2023)
Nowadays, global warming is a tremendous phenomena in the world. Every country trying to solve these conditions, including Indonesia that has a campaign to reduce the emission of CO and HC from vehicles. However, the number of vehicles is increasing every year. Based on that condition, the researchers are trying to modify the fuel with the additive. This work modified the gasoline with 10% ethanol additive addition and investigated the viscosity properties using Stokes law linear regression method and compared to pure gasoline. The viscosity properties are chosen by their effect on emission of vehicles. A low viscosity of fuel can reduce CO and HC in gas emission. Then, this work was finding that the viscosity of gasoline is decreased, but 10% of ethanol does not significantly change the characteristics of gasoline. Even so, the linear regression has successfully used as an analyzed method to determined the viscosity. Then, this finding also contributes to development of fuel in Indonesia to reduce the emission of CO and HC with the modified of gasoline using ethanol in the other concentration.